EU Contractual Protection of Creators: Blind Spots and Shortcomings - Dusollier, Séverine (The Columbia Journal of Law & the Arts, 2018)
One key objective of copyright is to grant exclusive rights to authors and creators to enable them to reap the full value of their creations. As a consequence, they should be able to transfer or license their rights to persons and companies more apt to exploit them commercially, thereby earning some revenues from such exploitation. Both United States1 and the European Union recognize the creator as the primary copyright owner. Because copyright is transferable, at least the economic rights, the work can transform into an economic asset whose rights are acquired by producers, publishers or other economic actors whose purpose is to make it available on the market. The creation then becomes a book, a film, a music album, a play. In most cases, producers and publishers take the risk and investment needed for the work to yield some revenue and provide access to the market for authors. The first modern copyright law, the U.K. Statute of Anne, recognized early on this reality, as its first provisions already mentioned the author and publisher side by side. Therefore, one of the first relevant acts accomplished by the author, after the creation itself, is to entrust someone else to commercially exploit her rights, hence to give up some part of control over her work. This first contract may be a tricky episode for creators as they will in most cases be in a weaker bargaining position, due to their inexperience, lack of information or desire to be published or produced at any cost. Conversely, commercial undertakings exploiting musical, audiovisual, literary or other works are generally better equipped—and more accustomed—than individual creators to draft contracts that protect their interests. The increasing concentration in the economic sector of entertainment and media strengthens even more their bargaining power and their possibility to impose unilateral and standard exploitation contracts that tend more and more to be so-called “adhesion contracts,” that are proposed to authors with no real margin for negotiation, on a take-it-or-leave-it basis. As cultural markets are considered by economists to be winner-take-all markets, they hold a great part of risk for creators and commercial exploiters alike, a risk that has even been increased in the digital environment with the piracy threat. As a result, only a few creators can earn a sufficient income out of their creation and it has been estimated that the top ten percent of the U.K. creators get about sixty to eighty percent of the total income of the creative profession. It will come as no surprise that, on average, incomes of creators are well below the median income. The current economic situation of creators in Europe, who will be directly affected by austerity policies and the ensuing reduction of culture funding, might further increase their vulnerability. The same could be said of countries outside of the European Union. The European Union has so far declined to harmonize the legal provisions aimed at protecting creators in the contracts they enter into,8 the matter being left to Member States. Some (e.g. Belgium, France, the Netherlands, Germany, Spain or Italy) have a detailed and protective set of legal provisions aimed at rebalancing the bargaining power between the creator and her publisher/producer. Other countries have no rules at all (e.g. U.K.) or only partial ones (e.g. Denmark). The legal protection that exists in some countries consists of default and mandatory rules that copyright contracts should comply with: they deal with transferability of rights (including the issue of moral rights), required formalities, restrictions on transfer of rights, obligations to specify the scope, duration, territorial scope and remuneration of the transfer, obligations of exploitation imposed to the person acquiring the rights, interpretation rules, and termination or revision of contract. Some specific provisions also apply to contracts applicable to defined categories of works, such as publishing contracts for literary works, production contracts for audiovisual works, etc. Additionally, the general rules of contract law can be used to confer more protection to the authors. As the area of contract law is less harmonized in the European Union, the rules will differ greatly from one Member State to the other, but could include the principles of good faith, fairness or equity, the prohibition of unfair terms, some principles of interpretation of contracts, the recourse to usage, etc. This paper is based on a study commissioned in 2013 by the European Parliament to assess the situation of European creators and the contractual protection conferred to them by E.U. Member States. Part I rapidly summarizes the legal provisions existing in some European countries that protect authors when transferring their copyright. Part II zooms out of the specific rules regulating the copyright contracts to draw the overall context of exploitation of creative works and of its many actors to challenge the central role that such national laws confer to the first contract entered upon between the creator and her publisher or producer. This insufficiency is illustrated by selected issues for which these specific rules are incapable to provide a satisfactory solution or protection to the author. Part III offers a conclusion in the form of some recommendations for a better treatment of creators when transferring their rights for exploitation of their works. These recommendations take into account the broader picture of exploitation of creative content and the shortcomings of the current legal provisions, when they exist.